Ground Zero(3): Inside the New American Home - Louise LACHAPELLE (E-REA)
This paper will continue the study of the reconstruction process on the World Trade Center’s site. In order to produce the site of catastrophe as a space where construction is possible it was necessary to rapidly exclude the reality of remains, wastes and other ruins. Ground Zero: Inside the New American Home will focus on the organization of collections related to the events of September 11 2001 by various museums (including collections involving museological conservation/conversion of remnants) and on a body of exhibitions. These collections and exhibitions produce a distance that lifts the ban to see or show the ruins, the remains, and contribute to recreate boundaries, as well as a familiar space, “the space of (safe) viewing” (Lilie Chouliaraki 2004), at the centre of a newly “secured” national and symbolic periphery, the space of “safe” living, “Inside the New American Home.”Inside the New American Home also continues to develop a critique of culture and of the ritual sense of art (Walter Benjamin, Écrits français 1940). If the rescue sought through the authority of the museum and its expertise in treating and disseminating “the truth” (Azoulay 2001) suggests a troubling collusion of powers (Klein 2007), it is less because their authority and expertise conserve the memory of an event than because they nurture the memory of an art which saves: in other words, a cultural strategy based on sacrifice. This paper will consider the role of such collections and exhibitions in relation with other post-9/11 mechanisms of cohesion and control, such as the Homeland Security Department, the Security Fence and the Secure Border Initiative, as well as the role of museums and a “war museology” in relation to these other cultural enclosing devices and domestic military strategies.